(untitled) (Advances in Systems Science and Applications, 2025)
The article proposes a generalization of the method of characteristics to quasilinear systems of evolutionary equations with one spatial variable. Such systems are a special case of hydrodynamic type systems. It is shown that in some cases self-intersection of solution graphs is possible. An example of a system of two equations is considered in detail.